2017
DOI: 10.1080/17421772.2017.1340663
|View full text |Cite
|
Sign up to set email alerts
|

Do jobs follow people or people follow jobs? A meta-analysis of Carlino–Mills studies

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 65 publications
0
20
0
3
Order By: Relevance
“…Thus it remains an empirical question as to who moves first, firms or residents. A meta‐analysis of this body of literature finds evidence for the jobs‐follow‐people theory but results across studies depend on the data, specification and variables (Hoogstra, van Dijk, and Florax, ). Our work, however, supports the idea that residents on Manhattan moved first and then office‐based firms followed them.…”
Section: Related Literatures and Theoriesmentioning
confidence: 99%
“…Thus it remains an empirical question as to who moves first, firms or residents. A meta‐analysis of this body of literature finds evidence for the jobs‐follow‐people theory but results across studies depend on the data, specification and variables (Hoogstra, van Dijk, and Florax, ). Our work, however, supports the idea that residents on Manhattan moved first and then office‐based firms followed them.…”
Section: Related Literatures and Theoriesmentioning
confidence: 99%
“…Indeed, a survey of business owners from firms that had moved in the last five years found that the crime and safety of a neighborhood are important for deciding on a new location, in addition to other measures of quality of life (Love and Crompton 1999). Studies on population-employment interactions also suggest that safety can influence business location and relocation decisions via population redistribution, while the literature is not unequivocal with regard to the question of whether jobs follow people or people follow jobs (Boarnet, Chalermpong, and Geho 2005;Hoogstra, van Dijk, and Florax 2017;Kim and Hewings 2013).…”
Section: Crime and Residential Mobilitymentioning
confidence: 99%
“…Il existe un grand nombre de travaux basés sur le modèle de Gerald A. Carlino et Edwin S. Mills (1987), qui étudient le lien entre les dynamiques locales de l'emploi et de la population. Cependant, les résultats des études empiriques varient beaucoup selon les données mobilisées et selon l'échelle géographique à laquelle les études sont menées (Hoogstra et al, 2017). Nous souhaitons dans ce travail déterminer si c'est la population qui suit l'emploi ou bien si c'est l'emploi qui suit la population, en faisant l'hypothèse qu'il existe une hétérogénéité au sein des dynamiques de l'emploi et de celles de la population.…”
Section: Une Analyse Spatiale Des Mouvements De L'emploi Et De La Popunclassified